The soul of a butterfly reflections on life's journey - Ali, Muhammad 1942-2016 (Simon & Schuster, 2004)
"During my boxing career, you did not see the real Muhammad Ali. You just saw a little boxing and a little showmanship. You saw only a part of me. After I retired from boxing my true work began. I have embarked on a journey of love, seeking truth, peace and understanding." So Muhammad Ali begins this spiritual memoir, his description of the values that have shaped and sustained him and that continue to guide his life. In The Soul of a Butterfly the great champion takes listeners on a spiritual journey through the seasons of life, from childhood to the present, and shares the beliefs that have served him well. After fighting some of the fiercest bouts in boxing history against Joe Frazier and George Foreman, today Muhammad Ali faces his most powerful foe--outside the boxing ring. Like many people, he battles an illness that limits his physical abilities, but as he says, "I have gained more than I have lost...I have never had a more powerful voice than I have now." Ali reflects on his faith in God and the strength it gave him during his greatest challenge, when he lost the prime years of his boxing career because he would not compromise his beliefs. Written with the assistance of his daughter Hana, The Soul of a Butterfly will provide comfort for our troubled times.
Keywords: Ali, Muhammad -- 1942-; Ali, Muhammad -- 1942-2016; Boxers (Sports) -- United States -- Biography; African American Muslims -- Biography; Spiritual biography -- United States; USA; Autobiografie